A Case Report on Parathyroid Adenoma - Kantharia, Shehnaz R.; Kantharia, Rajesh A.; Reddy, Pradeep K.; Mistry, Yogesh M. (New Horizons in Medicine and Medical Research Vol. 9, 2022)
Primary hyperparathyroidism is an endocrine pathology that affects calcium metabolism. Patients with primary hyperparathyroidism have high concentrations of serum calcium or high concentrations of parathyroid hormone, or incorrect parathyroid hormone levels for serum calcium values. In India, the prevalence of primary hyperparathyroidism is 2.5 per 1000 people. A non-cancerous parathyroid adenoma, hyperplasia, or, in rare cases, parathyroid carcinoma can induce primary hyperparathyroidism. The majority of these people have minimal or no symptoms. Correct diagnosis can be reached by clinical settings, biochemical and radiological tests and final confirmation by histopathology of the specimen. In comparison to classic bilateral neck exploration, minimally invasive parathyroidectomy is now the most routinely utilised surgical treatment for primary hyperparathyroidism. PTH monitoring during surgery is most beneficial as a supplement to preoperative imaging, allowing for more focused operations.